Population features of the invasive kelp Undaria pinnatifida (Phaeophyceae: Laminariales) in Nuevo Gulf (Patagonia, Argentina). - Casas, Graciela Noemi (2008)
The invasive kelp Undaria pinnatifida was observed for the first time in the Nuevo Gulf (Patagonia, Argentina) in December 1992. At the present time, with the exception of sandy bottoms, the coasts of the Nuevo Gulf are almost entirely colonized. From October 1997 to February 2000, the characteristics of this population, i.e. the relationships between morphological fea- tures and seawater temperature, the seasonality in sporophyll development and the proportions of different reproductive stages during its life cycle, were analysed. The observations confirmed that the maximal mean densities of sporophytes (149.1 plants m 2 2 ) occurred in winter while the mean tallest sporophytes (88.5 cm) and the mean highest biomass (16501 g m 2 2 ) were registered in spring and at the beginning of the summer. Coexisting juvenile and mature sporophytes were found. Sporophylls showed also seasonal characteristics, with maximal width in summer. Manipulative experiments conducted for testing the recruitment pattern of Undaria pinnatifida confirmed that the presence of juvenile individuals was uninterrupted. Thus, in this paper, we denote that U. pinnatifida has a constant recruitment, together with high repro-ductive rates, which are some of the characteristics of an introduced species, which explains why they became a highly invasive species or ‘pest species’, with negative environmental and economic effects.